Isolation and spectroscopic characterization of two isomers of the metallofullerene Nd@C-82 - Porfyrakis, K; Kanai, M; Morley, G; Ardavan, A; Dennis, T; Briggs, G (2005)
For the first time, two types of the metallofullerene Nd@C-82 have been isolated and characterized. HPLC was used to isolate Nd@C-82(I, II). The two isomers were characterized by mass spectrometry and UV-Vis-NIR absorption spectroscopy. Nd@C82(I) was found to be similar in structure to the main isomer of other lanthanofullerenes such as La@C-82, as was previously reported. We assign Nd@C-82(I) to have a C-2v cage symmetry. Nd@C-82(II) showed a markedly different UV-Vis-NIR absorption spectrum to Nd@C-82(I). Its spectrum is in good agreement with that of the minor isomer of metallofullerenes such as Pr@C-82. We therefore assign Nd@C-82(II) to have a C-s cage symmetry. In contrast to other metallofullerenes, both isomers appear to be equally abundant.